Collagen as extracellular matrix (ECM) for three-dimensional (3D) cell culture models: A mini-review - Mohd Esa, Norhaizan; Kamarudin, Ammar Akram; Zulhilmi Cheng, Mohamad Zulhafiz Shafiq (Universiti Malaysia Sabah, 2024)
In vitro cell culture models are crucial tools in drug discovery for understanding pathophysiology and cellular physiology. Traditionally, two-dimensional (2D) cultures have significantly advanced cell-based research. However, their translational potential is limited by their inability to replicate the natural cellular environment. The emergence of three-dimensional (3D) culture models offers more physiological relevance platforms to mimic a natural tissue architecture. Scaffold-based techniques that utilize extracellular matrix (ECM) components have become increasingly prominent, with collagen emerging as a leading candidate due to its structural and biological properties. Collagen, the key player of structural protein in connective tissue, may act as biomimetic scaffolds that facilitate cell aggregation, proliferation, and migration. This mini-review explores the unique features of collagen as a hydrogel scaffold, including its biocompatibility, natural abundance, and the capacity to replicate tissue-specific architectures.